Health-promoting Properties Infusions of Hibiscus Flowers and Selected Berry Fruit Processing By-products - Błaszczyk, Alfred; Sady, Sylwia; Płaczek, Zuzanna; Kawałek, Patrycja; Dłużniewska, Nikola; Pakuła, Karolina; Konopelski, Adam (Prozdrowotne właściwości naparów z kwiatów hibiskusa i wybranych produktów ubocznych przetwórstwa owoców jagodowych, 2023)
Aim: This study aimed to compare the health-promoting properties of hibiscus flowers infusions with pomace infusions from black chokeberry, blackcurrant, raspberry and strawberry. Methodology: Five types of fruit pomace infusions were selected as the research material: hibiscus flowers infusion and infusions from black chokeberry, blackcurrant, raspberry and strawberry pomace. The total polyphenol content, antioxidant activity and colour parameters were determined. Results: The highest content of phenolic compounds was found in hibiscus flowers infusion (453.25 mg GAE/L of infusion). Hibiscus flowers infusion also showed the highest antioxidant activity measured by DPPH, ABTS and FRAP tests. Among the tested infusions from selected berry fruit by-products, the infusion from chokeberry pomace was characterised by a high content of total phenolic compounds and antioxidant activity. The lowest total phenol content and antioxidant activity were found in the strawberry pomace infusion. Implications and recommendations: Despite their popularity and variety of flavours, commercial fruit teas that use fruit by-products need to be standardised in terms of their health-promoting content. This means that there is no uniform, controlled standard that specifies the amount of specific beneficial health-promoting ingredients in each package of fruit tea. The authors’ future research related to hibiscus flowers and berry pomace will focus on the influence of organoleptic characteristics on biological activity and the standardisation of the developed tea prototypes in terms of the content of health-promoting substances. Originality/value: According to the research, hibiscus flowers infusion has the highest antioxidant and colouring properties. Chokeberry pomace infusion showed antioxidant properties comparable to hibiscus flowers infusion. Consequently, the health-promoting properties and low cost of fruit processing by-products may contribute to their broader use in the tea industry.
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2023, Nr 39, s. 65-74
Keywords: hibiscus flowers; fruit pomace; health-promoting properties; infusions; upcycling; circular economy; kwiaty hibiskusa; wytłoki owocowe; właściwości prozdrowotne; napary; waloryzacja produktów ubocznych; gospodarka o obiegu zamkniętym